2014
DOI: 10.1159/000367859
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Abscess in Crohn's Disease: Multidisciplinary Management

Abstract: Crohn's disease (CD) is characterized by full-thickness inflammation of the bowel. For this reason, perforating complications such as intra-abdominal abscesses or fistulas are common. A concomitant intra-abdominal abscess with active CD of the small bowel is a challenging dilemma for gastroenterologists and surgeons. Since there is active and severe disease, this should be treated with immunosuppressive drugs. However, in the presence of an intra-abdominal abscess, immunosuppression can be dangerous. There are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 28 publications
0
42
0
4
Order By: Relevance
“…Concerning the surgical approach the present case did not meet the criteria for a safe laparoscopic procedure (9-15), due to its large diffusion in the soft tissues and the enteric quality of the collection. In the present case our approach appears in line with the indications of the literature (4,5,9,16). The bowel was resected removing the diseased segment of terminal small bowel and ileo-cecal junction as indicated in the most part of experiences (5,9,11,12).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Concerning the surgical approach the present case did not meet the criteria for a safe laparoscopic procedure (9-15), due to its large diffusion in the soft tissues and the enteric quality of the collection. In the present case our approach appears in line with the indications of the literature (4,5,9,16). The bowel was resected removing the diseased segment of terminal small bowel and ileo-cecal junction as indicated in the most part of experiences (5,9,11,12).…”
mentioning
confidence: 57%
“…The full thickness inflammation of the intestinal wall develops in strictures, fistulas and abdominal abscesses (1)(2)(3)(4). These are the most common complications during the course of the illness (5) and surgical treatment is frequently required in these occurrences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, following abscess resolution, 60 % of patients could be started on thiopurines and 9 % on biologics, while in 31 %, baseline therapy was not modified. While percutaneous drainage is increasingly used, by itself or as a bridge to surgery, as treatment of intraabdominal abscesses in CD [90], in one study, it was found that only one third of abscesses treated with percutaneous drainage showed long-term resolution compared to 90 % of those undergoing immediate surgical drainage [91]. In a meta-analysis of CD patients in remission, neither sulfasalazine nor mesalamine were effective in preventing relapse in patients with quiescent CD, but in a per protocol analysis, mesalamine appeared to reduce risk of relapse (RR=0.79; 95 % CI=0.66-0.95, NNT=13) [68].…”
Section: Azathioprine and Other Immunosuppressants May Induce Remissimentioning
confidence: 99%